KAJIAN KELAYAKAN SISTEM FOTOVOLTAIK DI KAMPUNG MANDIRI ENERGI - Aripriharta -; Dwi Mukti Asmoro; Muhammad Jazuli Shubhi; M Rodhi Faiz; Langlang Gumilar (Power Elektronik : Jurnal Orang Elektro, 2023)
Electrical energy is a vital need and very important for modern society. Not only in big cities, electrical energy has become a big part of the survival of village or village communities. Recently,  Renewable Energy (EBT) has been developed to fulfil the demand for electrical energy as a strategic energy source that is useful in anticipating an energy crisis. This study analyzes the feasibility of village-scale solar power plants (PLTS) with a capacity of 11.25 kWp using PVsys software, the system uses 45 pv 250 WP, 9000 Watt Inverter, 2 SCC with a capacity of 5000 W, a battery of 2,400 Ah. The output of the system show is 46.90 kWh per day. The power was used to supply 38 houses with an average load requirement of 35.3 kWh per day or 1 kWh per house. In the PLTS system designed along with economic analysis in the form of an investment value or PWA of IDR 282,674,638, the BEP value is reached in the 12th year, the Net Present Value (NPV) is IDR 9,447,427. The cost of energy is IDR 25,678,500/ year.